SYSTEM OF BANKING MARKETING: THEORETICAL APPROACHES AND TRENDS OF MODERN PRACTICE - Babukh, Ilona; Nikiforov, Petro (Миколаївський національний університет імені В.О. Сухомлинського, 2018)
Current trends in the theory and practice of banking marketing are analyzed. A brief description of the banking services market is given, specific features of the banking product are indicated. The role of the bank in the market of models В2С, В2В, В2G is shown. It is noted that in the market of banking services there is a transition from classical marketing concepts to marketing, built on a client-oriented approach, forming customer loyalty through innovative marketing ideas, the use of information technology, the Internet. Also is considered the influence of the level of corporate culture on the bank's image, on various aspects of the bank's marketing activities, including in the moral and ethical plane
СИСТЕМА БАНКОВСКОГО МАРКЕТИНГА:ТЕОРЕТИЧЕСКИЕ ПОДХОДЫ И ТЕНДЕНЦИИ СОВРЕМЕННОЙ ПРАКТИКИ
Keywords: bank marketing; market of banking services; market models (В2С, В2В, В2G); trust; customer orientation; corporate culture